A Smartphone Is Not Enough: Telehealth Attendance and the Digital Divide - James Labadorf; Matthew Nichols; Tayana Williams; Celina Cunanan; Brian D'Anza (Health Care Science)
ABSTRACT Background Telehealth has emerged as a powerful tool for managing chronic diseases and mental health conditions, offering increased access to care and improved patient outcomes. However, inequities in digital connectivity and technological resources have created significant disparities in access to these potentially life‐changing services, disproportionately impacting marginalized and minoritized communities across the globe. Methods Data on 473,716 telehealth encounters occurring between January 1, 2022, and June 30, 2023 were retrieved from the electronic health records (EHR) system used by University Hospitals. These encounters were classified into three groups: attended, canceled, and no‐show. Relative risk was calculated based on age, sex, and race, and a multivariate linear regression was performed with age, sex, and race as inputs, to determine their effect on the encounter outcome. Results Our analysis identified significant differences in relative risk between demographic groups. Patients 20–39 years of age had a high relative risk of cancellation and no‐show, and Black patients demonstrated the highest relative risk for cancellation and no‐show. The regression analysis illustrated a statistically significant link between no‐shows and patients with a cellular plan with no other internet subscription (p < 0.001), smartphone ownership (p < 0.001), and not having a computer (p < 0.05). Conclusions This study highlights the clinical repercussions of the digital divide, as patients relying on a mobile phone and data plan to attend telehealth visits were more likely to no‐show. Current disparities in digital connectivity for historically marginalized populations heightens the risk of creating a digital underclass. There is evidence this study may be applicable in multiple countries across the world. Further research on the causes of the observed no‐shows is necessary to ensure equitable delivery of digital healthcare services.